Oral monophthong vowel qualities of the Jamee language in Aceh - Yusuf, Yunisrina Qismullah; Fata, Ika Apriani; Karwinda, Sinta (Universitas Pendidikan Indonesia, 2021)
Jamee language is one of the languages spoken in Aceh Province, in the super-diverse country, Indonesia. Previous studies have noted inconsistencies in the number of oral monophthong vowels produced by the Jamee speakers. Accordingly, this research aims to investigate the qualities of the oral monophthong vowels of the Jamee language that are still spoken today. Ten female speakers were chosen as the informants to provide data for this research. They were recorded to produce words that contained the target vowels. The recordings were then transferred to Praat software in spectrograms, and measurements on the midpoint of each vowel for their F1 and F2 in Hertz were conducted. In Excel, the measurements were converted in the Bark scale, and the average values of each vowel were plotted on an F1-F2 chart. The results further showed that there are currently seven monophthong vowels in this language, they are /i/, /e/, /É›/, /a/, /o/, /u/ and /â†„/. This acoustic study has calculated the approximate measurements for the vowels based on their F1 and F2 from the spectrograms in Praat. The qualities of these vowels are /i/ with F1 = 463 Hz and F2 = 2484 Hz, /e/ with F1 = 550 Hz and F2 = 2493 Hz, /É›/ with F1 = 641 Hz and F2 = 2412 Hz, /o/ with F1 = 535 Hz and F2 = 1434 Hz, /â†„/ with F1 = 713 Hz and F2 = 1312 Hz, /u/ with F1 = 489 Hz and F2 = 1165 Hz, and finally /a/with F1 = 887 Hz and F2 = 1898 Hz. The findings of this research are seen as pivotal in the field of phonology as it assists linguists in documenting and preserving a minority language in Aceh Province, Indonesia.